Understanding Factors Impacting Behavioral Intention and Use Behavior of Online Art Exhibitions Among Art Students in Sichuan, China - Zhai, Yitao (ABAC ODI JOURNAL Vision. Action. Outcome, 2024)
This study aims to explore the factors impacting students in art majors in Chengdu universities to use online art exhibitions. The framework proposes seven variables of causal relationships, including subjective norms, perceived ease of use, perceived usefulness, behavioral intention, perceived behavioral control, social impact, and behavior. The researcher applied quantitative methods to distribute questionnaires to 517 participants. Before issuing the questionnaire, the validity and reliability of the data were tested using the Index of item objective congruence (IOC) and Cronbach’s alpha for the pilot tests (n=50). The data are analyzed by confirmatory factor analysis (CFA) and structural equation model (SEM) to verify the model’s goodness of fit and confirm the causal relationship between the hypothesis test variables. The results show that subjective norms have a significant impact on perceived usefulness, perceived ease of use has a significant impact on perceived usefulness, perceived ease of use has a significant impact on behavioral intention, perceived usefulness has a significant impact on behavioral intention, perceived behavioral control has a significant impact on behavioral intention, social impact has a significant impact on behavioral intention. The behavioral intention has a significant impact on behavior. The seven hypotheses have been proven to meet the research objectives. Therefore, the study of conceptual models can predict and explain the behavioral intention of using online art exhibitions in higher education.